The usage of animation programme in arabic language learning and its effect on vocabulary recall and basic verbal skills : a case study at Al Amin Gombak Islamic Primary School - Mahani binti Mokhtar
This research aimed to investigate the effectiveness of the usage of animation programme in Arabic language learning and its effect on vocabulary recall and basic verbal skills among the first year students in Al-Amin Gombak Islamic Primary School. To answer the questions of the study, the researcher adopted the experimental approach. Two classes of similar academic level were selected. One class was the experimental group whilst the other, the control group. Animation was used with the experimental group, while normal teaching tecniques were used with the control group. The study was done during the second term of the school year 2016. The vocabulary recall tests consisted of twenty (20) words whist the verbal skills test consisted of six (6) sentences. Descriptive analyses was done on the data. The results showed that level of effectiveness of the usage of animation programme in achieving the objectives of this study. In the light of those findings, the study urged the usage of animation programmes in Arabic language learning for primary school students to enhance the learning of vocabulary and basic verbal skills, not as an alternative but as an additional technique. It was also suggested that further researches be done on how to maximise the usage of animation programmes in Arabic Language Learning in primary school and what kind of animation programmes would be most effective in Arabic language learning amongst primary school students.